Strategi Komunikasi Pemasaran Dinas Kebudayaan dan Pariwisata Kota Surakarta dalam Meningkatkan Minat Kunjungan Wayang Orang Sriwedari Tahun 2024 - Ray Dhiana; Tanti Hermawati (Jurnal Komunikasi Massa, 2024)
This research is influenced by the importance of marketing communication strategies in increasing interest in visiting Wayang Orang Sriwedari in Surakarta City, especially in the 2018-2024 period. The purpose of this research is to find out how the Surakarta City Culture and Tourism Office designs and implements effective marketing communication strategies to attract public interest in Wayang Orang Sriwedari performances. The theories used in this research include the stages of marketing communication strategy and marketing communication mix. This research also refers to the stages of planning, situation analysis, determining targets, setting communication objectives, determining messages, media selection, and evaluation expressed by Fred R. David. In addition, this research also analyses the five marketing communication mixes by Kotler which includes advertising, sales promotion, public relations, personal selling, and direct marketing. The research method used is a qualitative approach and case study method. Data were collected through in-depth interview techniques and documentation, which allowed researchers to explore in-depth information about the strategies implemented by the Surakarta City Culture and Tourism Office. The results showed that the Surakarta City Culture and Tourism Office has implemented seven stages of marketing communication strategies and has succeeded in increasing interest in visiting Wayang Orang Sriwedari, with an increase in public awareness and participation in performances. The conclusion of this research is that the implementation of an appropriate and planned marketing communication strategy that has been implemented by the Surakarta City Culture and Tourism Office in 2024 can have a positive impact on increasing interest in visits in the culture and tourism sector. This research is expected to provide input for the development of marketing communication strategies in the future.